PERANAN ISOZIM PROTEIN KINASE C-ΑLFA DALAM MEMEDIASI EFEK ANTIPROLIFERASI ALFA-TOKOFEROL PADA SEL STROMA PROSTAT - Purnomo, Basuki B (Indonesian Urological Association, 2009)
Objective: Alpha tocopherol, other than its anti-oxidant activity, also has a non anti-oxidant activity that correlates with inhibition of PKC-alpha isozyme activity. Several studies had confirmed its role in inhibition of vascular smooth muscle proliferation. Inhibition of stromal cell proliferation is an alternative method of prevention in BPH development. The aim of this in vitro study is to confirm that alpha-tocopherol, by its ability to inhibit PKC-alpha activity, has the capability to inhibit human prostatic stromal cell proliferation rate. Materials & Method: Primary cultures of human prostatic stromal muscle cells were obtained from 4 patients with bladder outlet obstruction caused by benign prostatic enlargement. The effects of various concentrations of alpha-tocopherol (20, 30, 40, 50, and 60 microM) were examined by cell proliferation and PKC-alpha isozyme activity assay. Cell proliferation study was performed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay method. Caspase-3 activity assay was also performed to examine apoptotic mechanism. Results: MTT method, which is used to count viable cells, showed that exposures to various doses of alpha-tocopherol resulted in decreased proliferation rate. The decrement of proliferation rate is linear with the increment of alpha-tocopherol dose. Immunocytochemistry staining with anti caspase-3 antibody showed that no cells developed apoptosis. Alpha-tocopherol also inhibits PKC-alpha activity. Isozyme activity is reduced along with the increment of the dose (dose-dependent). There is a correlation between PKC-alpha activity with cell proliferation rate after exposure to alpha-tocopherol (R2=0,9279; p=0,000). Conclusion: Alpha-tocopherol at different concentrations reduces prostatic stromal cell proliferation rate, without effect on apoptosis. This antiproliferative property correlates with decreased activity of PKC-alpha isozyme.